Self Presentation of Communist Albania Through the Antagonist Discourse (European Journal of Interdisciplinary Studies, 2016)
Given the fact that totalitarian systems use the media as the most powerful tool to produce and disseminate the ideology, the text of this paper is the printed press of that period. I especially selected the journal Zëri i Popullit (Voice of People), as it was the main representative press organ of Communist Party which would later become the Labor Party. Understanding the past discourses paves the ground for understanding their continuity or their change during the new systems of governance as it will be after 1990's in Albania. The methodology of this paper is Critical Discourse Analyze. I will use Critical Discourse Analyze at the same time as theory for this study. Since the totalitarian system ruled Albania during that period, the study will be focused on analyzing the hegemonic discourse, seeing antagonism as the basic form of power’s self presentation. Also to understand the key moments of self presentation I have selected the articles during the national holidays such as 1st of May the Labor Day 28th of November the Independence Day and 29th of November the Liberation Day. The articles of press during national holidays are selected as key data, because these dates have always been important to deliver messages. This paper aims to establish discursive categories seeing antagonism as main feature of power legitimacy. Based on this argument the research question of this paper is; which are the elements used by printed press for its self presentation to legitimize the power?